The labor market returns to "first in family" university graduates - Anna Adamecz-Völgyi; Morag Henderson; Nikki Shure (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
We examine how first in family (FiF) graduates (those whose parents do not have university degrees) fare on the labor market in England. We find that among women, FiF graduates earn 7.4% less on average than graduate women whose parents have a university degree. For men, we do not find a FiF wage penalty. A decomposition of the wage difference between FiF and non-FiF graduates reveals that FiF men earn higher returns on their endowments than non-FiF men and thus compensate for their relative social disadvantage, while FiF women do not. We also show that a substantial share of the graduate gender wage gap is due to, on the one hand, women being more likely to be FiF than men and, on the other hand, that the FiF wage gap is gendered. We provide some context, offer explanations, and suggest implications of these findings.
Keywords: I24; I26; J24; 330; socioeconomic gaps; intergenerational educational mobility; higher education; labor market returns; gender economics